INCREASING CROP YIELDS: EFFECTIVE METHODS OF DRIP IRRIGATION IN AGRICULTURE - Chorshanbiyev Panji Khudoymuratovich (American Journals, 2024)
This scientific article examines effective methods and best practices of drip irrigation in agriculture. By exploring the principles of drip irrigation system design, maintenance, planning and management, this study explores how farmers can optimize water use efficiency, promote crop growth and achieve sustainable agricultural outcomes through the strategic implementation of drip irrigation systems. explains the possibility.
Keywords: Drip irrigation, agriculture, characteristics of drip irrigation, drops.